Дослідження методів, алгоритмів та створення програмного комлексу управліня жестами - Черепухін, Г. О. (ХНУРЕ, 2020)
In modern science and technology in solving a number of problems there is a need to use natural methods of human-computer interaction, the so-called natural interfaces. However, there is still no single definition of such interfaces and there are different approaches to classifying and ordering natural interfaces. This works aims to define and develop such methods to be used